A CONCEPTUAL APPROACH TO THE DEVELOPMENT OF THE DIDACTIC-METHODICAL COMPETENCE OF THE FUTURE PRIMARY SCHOOL TEACHER (World Bulletin of Social Sciences, 2023)
This article contains necessary information for students of higher educational institutions and teachers of primary education. This article discusses conceptual approaches to the development of the didactic-methodical competence of the future primary school teacher